Pokémon. Sword & shield. Volume 5 - Kusaka, Hidenori; Tanzer, Molly (Pokémon, 2022)
"Casey Shield, a hacker who invented the Dynamax Simulator, and Henry Sword, a boy who repairs gear for Pokémon, both dream of entering the Galar region's Gym battles. For Casey, it's a chance to reunite with her lost Pokémon. For Henry, it's an opportunity to search for the legendary Rusted Sword and Rusted Shield. The Gym challenges continue as Henry's battle against Allister of Stow-on-Side rages on! Next, both Henry and Casey must prepare for a match against another powerful gym leader! Will Henry and Casey ultimately be victorious against Opal of Ballonlea?!"--back cover